2015
DOI: 10.1142/s179354581550042x
|View full text |Cite
|
Sign up to set email alerts
|

The rapid determination of volatile fatty acid number in para rubber latex using fourier transform-near infrared spectroscopy based on quantification and discrimination model

Abstract: Volatile Fatty Acid number (VFA no.) is one of the parameters indicating the state of quality of Para rubber latex at that particular time. Most factories analyze this parameter using standard analytical method as in ISO 506:1992(E). Nevertheless, this procedure is complicated, chemical and time consuming, as well as skilled analyst required. Therefore, near infrared (NIR) spectroscopy which is rapid, accurate and nonchemicals method was applied to determine the VFA no. in¯eld latex and concentrated latex base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…13,14 They are components of the isoprene unit of rubber. 9,11 Based on the established data from Workman and Weyer, 17 the obvious peaks at about 5823 cm −1 (1717 nm) was due to functional group C–H methylene for hydrocarbons, 5230 cm −1 (1912 nm) due to P–OH phosphate (.P–OH) for phosphate, 4613 cm −1 (2168 nm) due to CONH 2 for proteins and 4335 cm −1 (2307 nm) due to C–H methylene associated with linear aliphatic hydrocarbon.
Figure 2.(a) Raw PV spectra, (b) thin film spectra and (c) thick film spectra.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 They are components of the isoprene unit of rubber. 9,11 Based on the established data from Workman and Weyer, 17 the obvious peaks at about 5823 cm −1 (1717 nm) was due to functional group C–H methylene for hydrocarbons, 5230 cm −1 (1912 nm) due to P–OH phosphate (.P–OH) for phosphate, 4613 cm −1 (2168 nm) due to CONH 2 for proteins and 4335 cm −1 (2307 nm) due to C–H methylene associated with linear aliphatic hydrocarbon.
Figure 2.(a) Raw PV spectra, (b) thin film spectra and (c) thick film spectra.
…”
Section: Resultsmentioning
confidence: 99%
“…9 and Hock and Sirisomboon 10 used this technique to evaluate the dry rubber content of latex. Narongwongwattana et al., 11 Sirisomboon et al. 12 and Narongwongwattana et al.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Narongwongwattana et al [25] reported that most factories analysed VFA number by the method in ISO 506:1992(E). However, the procedure was complicated, time and chemical consuming and also skilled technician required.…”
Section: Volatile Fatty Acid Numbermentioning
confidence: 99%